D. W. Jeffries, Jack Poffenbarger, and Carl E. Dixson, 1960. - (:unkn) unknown (Forsyth County Public Library, 2009)
WSJ 5-22-60 p.D12.
D. W. Jeffries, Jack Poffenbarger, and Carl E. Dixson, 1960. The President's Cup of the Philco Corporation was presented to Carl E. Dixson, executive vice-president of Brown-Rogers-Dixson Company.
Keywords: Forsyth County (N.C.) -- History -- Pictorial works; Forsyth County (N.C.) -- History -- Sources; Digital Forsyth